2007
DOI: 10.1093/carcin/bgm238
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent interactions of BLM and 53BP1 are required for their anti-recombinogenic roles during homologous recombination

Abstract: Mutations in bloom helicase protein (BLM) helicase cause Bloom syndrome, characterized by predisposition to almost all forms of cancer. We have demonstrated previously that endogenous BLM, signal transducer 53BP1 and RAD51 are present in a complex during replication stress. Using full-length recombinant proteins, we now provide evidence that these proteins physically interact. BLM interacts with checkpoint kinase (Chk) 1 via the kinetochore-binding domain (KBD). Wild-type (WT) Chk1 phosphorylates 53BP1 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Using an in vitro GST pulldown assay, we found that full-length BLM and RAD54 directly interacted. Using purified BLM fragments (Tripathi et al, 2008), we further demonstrated that the N-terminal 212 amino acids of BLM mediated this interaction (Fig. 2B).…”
Section: Blm and Rad54 Physically And Functionally Interact During Hrmentioning
confidence: 76%
See 2 more Smart Citations
“…Using an in vitro GST pulldown assay, we found that full-length BLM and RAD54 directly interacted. Using purified BLM fragments (Tripathi et al, 2008), we further demonstrated that the N-terminal 212 amino acids of BLM mediated this interaction (Fig. 2B).…”
Section: Blm and Rad54 Physically And Functionally Interact During Hrmentioning
confidence: 76%
“…Hence, the question arises: how does BLM switch its function from a prorecombinogenic to an anti-recombinogenic protein? We have recently demonstrated that lack of ATR-mediated BLM phosphorylation on Thr99 prevents the helicase from disrupting RAD51 polymerization (Tripathi et al, 2008). Additional cellular and molecular event(s) including additional post-translational modification(s) on BLM and/or interaction with other antirecombinogenic proteins, such as 53BP1 and p53 (Sengupta et al, 2003;Tripathi et al, 2007) might also be required during this transition process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinants and siRNA pGEX4T-1 BLM (1-1417) (Srivastava et al, 2009), pGEX4T-1 BLM (1-212), pcDNA3 Flag BLM (gift from Ian Hickson), EGFP-C1 BLM (gift from Nathan Ellis), pGEX4T-1 BLM (191-660), pGEX4T-1 BLM (621-1041), pGEX4T-1 BLM (1001-1417) (Tripathi et al, 2008). pSG5-Jun (gift from Bohdan Wasylyk).…”
Section: Methodsmentioning
confidence: 99%
“…BS patients exhibit defects in DNA replication and homologous recombination events, manifested by an increased frequency of sister chromatid exchanges (SCEs) (Chaganti et al, 1974). BLM regulates homologous recombination by a number of mechanisms, such as disruption of RAD51 nucleofilaments (Bugreev et al, 2007;Tripathi et al, 2007), prevention of chromosome breakage (Russell et al, 2011), recruitment of p53 to carry out its own functions during homologous recombination (Sengupta et al, 2003) and enhancement of the interactions between 53BP1 and RAD51 (Tripathi et al, 2008;Tripathi et al, 2007). BLM is involved in the recognition of the DNA damage by a K63-linked ubiquitindependent mechanism (Tikoo et al, 2013), transmission of the damage signal to the repair proteins and in repair of the DNA damage during the effector phase (Tikoo and Sengupta, 2010).…”
Section: Introductionmentioning
confidence: 99%